2018
DOI: 10.1017/nws.2018.14
|View full text |Cite
|
Sign up to set email alerts
|

A study of cascading failures in real and synthetic power grid topologies

Abstract: Using the linearized DC power flow model, we study cascading failures and their spatial and temporal properties in the US Western Interconnect (USWI) power grid. We also introduce the preferential Degree And Distance Attachment (DADA) model, with similar degree distributions, resistances, and currents to the USWI. We investigate the behavior of both grids resulting from the failure of a single line. We find that the DADA model and the USWI model react very similarly to that failure, and that their blackout cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
(77 reference statements)
2
11
0
Order By: Relevance
“…2(a),(b), with data points condensed around two regions: either causing severe damage of G ∈ [0.3; 0.6] or inducing no cascading failure. Similar bimodal behavior has been reported for cascading failures in the US Western Interconnect (USWI) power grid [19].…”
Section: Sensitivity To Target Selection In Spatially-localized Multisupporting
confidence: 77%
See 2 more Smart Citations
“…2(a),(b), with data points condensed around two regions: either causing severe damage of G ∈ [0.3; 0.6] or inducing no cascading failure. Similar bimodal behavior has been reported for cascading failures in the US Western Interconnect (USWI) power grid [19].…”
Section: Sensitivity To Target Selection In Spatially-localized Multisupporting
confidence: 77%
“…Prior studies on cascading failures in power grids suggest that power grid blackouts follow a first-order phase transition [18]. Similarly, a recent study conducted on the US Western Interconnect power grid has revealed that the probability of cascading failures occurring, with respect to the value of the tolerance parameter, exhibits a bimodal nature, characteristic to first-order transitions [19]. These results indicate that a disruption in the system can either cause insignificant damage or trigger severe cascading failures.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…In fact, islanding, i.e. separating the power grid into disconnected independent parts can be an efficient tool for stopping cascade propagation [66,123]. Moreover, Ref.…”
Section: Cascade Of Failures In Interdependent Networkmentioning
confidence: 99%
“…Therefore, great consideration was given to the study of interdependent networks and in particular their robustness, using percolation theory [14][15][16][17][18][19][20][21][22][23][24][25]. Such studies have been carried out to analyze cascading failures resulting from various attacks [26][27][28][29][30][31][32]. One of the key results in these types of studies is that often localized attacks are significantly more effective when compare to random attacks.…”
Section: Introductionmentioning
confidence: 99%